Time Course of Endothelial Dysfunction Induced by Decompression Bubbles in Rats - Zhang, Kun; Wang, Mengmeng; Wang, Haowen; Liu, Yinuo; Buzzacott, Peter; Xu, Weigang (Frontiers in Physiology, 2017)
Decompression stress can cause endothelial injury, leading to systematic inflammation and prothrombotic phenomena. Our previous work found that endothelial injury following decompression correlated positively with bubble formation. This study aimed to investigate the time course of endothelial injury and the relationship with bubble amounts. Rats were subjected to a simulated air dive to 7 ATA for 90 min with rapid decompression. Bubbles were detected ultrasonically at the root of pulmonary arteries following decompression. Surviving rats were randomly divided into six groups according to sampling time following decompression (2 h, 6 h, 12 h, 24 h, 48 h, and 72 h). Three parameters, serum levels of malondialdehyde (MDA), endothelin-1 (ET-1) and intercellular cell adhesion molecule-1 (ICAM-1) were identified from our previous study and measured. The level of MDA reached a peak level at 12 h post decompression, and then decreased gradually to control level before 72 h. For both ET-1 and ICAM-1, the greatest expression appeared at 24 h following surfacing, and the increases lasted for more than 72 h. These changes correlated positively with bubble counts at most detection time points. This study reveals the progress of endothelial dysfunction following decompression which provides guidance for timing the determination at least for the current model. The results further verify that bubbles are the causative agents of decompression induced endothelial damage and bubble amounts are an objective and suitable parameter to predict endothelial dysfunction. Most importantly, levels of endothelial biomarkers post dive may serve as sensitive parameters for assessing bubble load and decompression stress.